A curing agent for improving the water stability of phosphogypsum and its application

By adding a specific curing agent to the phospholosifying, a modified phosphor gypsum is formed to solve the problem of durability and water stability of phosphide gypsum in the road -based filler, and achieve higher route performance and environmental protection.

CN116282994BActive Publication Date: 2025-01-28ANHUI LIUGUO CHEM CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310126113.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-01-28
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

Phosphogypsum has long-term durability problems, poor water stability and water pollution problems in roadbed fillers, resulting in roadbed sinking or cracking, affecting the stability of the roadbed.

Method used

A curing agent, including mineral powder, lime, batteries, polycarboxylic acid water reduction agent, water absorbent, waterproofing agent, and albate, and mixed with phospholol to form modified phospholosypsum to improve its water stability and strength.

Benefits of technology

It significantly improves the water stability and intensity of phosphide gypsum, so that it can be used for road -based fillers under a certain pressure, meet the technical requirements of the technical details of the road surface grassroots construction, and reduce the amount of soluble P and F, ensure environmental protection environmental protection Require.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116282994B_ABST
    Figure CN116282994B_ABST
Patent Text Reader

Abstract

The present invention discloses a curing agent for improving the water stability of phosphogypsum and its application. The components of the curing agent for improving the water stability of phosphogypsum of the present invention include lime, carbide slag, polycarboxylic acid water reducer, water-absorbing swelling agent, waterproofing agent, metakaolin and mineral powder, and then the curing agent is mixed with the phosphogypsum pretreated with citric acid solution to obtain modified phosphogypsum. The curing agent prepared by the present invention is added to the phosphogypsum, so that the modified phosphogypsum after curing has good water stability and high strength, can be used as roadbed filler under a certain degree of compaction and meet the technical requirements for roadbed filler in JTG / TF20-2015 "Technical Specifications for Highway Pavement Base Construction"; and the modified phosphogypsum of the present invention ensures the environmental protection requirements of phosphogypsum filler for roadbed filling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of highway engineering, and in particular relates to a curing agent for improving the water stability of phosphogypsum and application thereof. Background Art

[0002] The production of phosphogypsum is closely related to the output of phosphate fertilizer. Phosphorus, as the main component of phosphate fertilizer in agricultural production, is directly related to the yield and quality of crops. At present, China is the world's largest producer of phosphate fertilizer. At the same time, a large amount of "by-products" - phosphogypsum - are produced in the process of preparing phosphate fertilizer. Phosphoric acid is extracted from phosphate rock by decomposing sulfuric acid, and phosphogypsum is produced as a by-product in the production process. Phosphoric acid is one of the main raw materials for the production of high-concentration phosphate compound fertilizers. The production of 1 ton of phosphoric acid (100% P2O5) produces about 5 tons of phosphogypsum, and the main component of phosphogypsum is calcium sulfate dihydrate. Due to its large quantity and complex and difficult-to-use characteristics, most phosphogypsum is currently handled in the form of "stacking". The stacking of these phosphogypsums not only occupies a large amount of land, but also poses certain environmental risks and safety hazards.

[0003] A lot of research has been carried out at home and abroad on the comprehensive utilization of phosphogypsum, and a large number of potential application methods have been proposed, mainly in the fields of building materials, road traffic materials, etc.

[0004] In the field of building materials, phosphogypsum can be used as a retarding component of silicate cement by utilizing its high CaSO4·2H2O content, and can form a new cementitious material system with waste containing active alumina. When phosphogypsum is used as a retarding component of cement, it may affect the performance of cement due to the large amount of impurities contained in phosphogypsum, and the retarding component only accounts for a small part of the cement mass. Therefore, this method is actually very limited and cannot consume a large amount of phosphogypsum.

[0005] In the field of road traffic materials, phosphogypsum is mainly used as roadbed filler. Qian Zhengfu et al. demonstrated the feasibility of using phosphogypsum for roadbed filling based on indoor experiments, unconfined compressive strength tests, dry-wet cycle tests, freeze-thaw cycle tests, etc., and Tang Qingqian et al. demonstrated the feasibility of using phosphogypsum for roadbed filling based on indoor experiments and engineering applications. Based on domestic and foreign data, there are the following problems when using phosphogypsum directly in roadbed materials. First, the long-term durability of phosphogypsum filler. There is no data reported so far, and it is impossible to judge the long-term stability of the filler. Second, phosphogypsum is greatly affected by water. When the water content is high, phosphogypsum will become soft and the strength will decrease, causing the roadbed to sink and lead to road damage. When the water content is low, shrinkage cracking will occur, which will also lead to road damage. Third, there is the water pollution problem of phosphogypsum. Therefore, improving or solidifying phosphogypsum so that it can be used as roadbed filler can not only consume phosphogypsum on a large scale, but also save sand and gravel materials, thereby achieving multiple benefits such as environmental protection, resource conservation, green development and reduced investment. Summary of the invention

[0006] The purpose of the present invention is to invent a curing agent for improving the water stability of phosphogypsum and its application in view of the problems existing in the prior art. The curing agent is added to phosphogypsum so that the cured modified phosphogypsum has good water stability and high strength, and can be used as a roadbed filler under a certain degree of compaction and meet the technical requirements for roadbed fillers in JTG / T F20-2015 "Technical Specifications for Highway Pavement Base Construction".

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A curing agent for improving the water stability of phosphogypsum, comprising the following components in parts by weight:

[0009]

[0010] The mineral powder is a gelling agent, and lime, carbide slag, polycarboxylic acid water reducer, water-absorbing swelling agent, waterproofing agent and metakaolin are additives.

[0011] The water-absorbing swelling agent is selected from a mixture of any one or more of sodium alginate, sodium carboxymethyl cellulose, and starch grafted acrylic acid copolymer.

[0012] The waterproofing agent is selected from any one or more of sodium methyl silicate, hexadecyltrimethylammonium chloride and sodium stearate.

[0013] The lime described in the present invention is slaked lime powder, the main component of which is calcium hydroxide, the chemical formula of which is Ca(OH)2, and the appearance of which is white powder, and the performance index of which meets the relevant provisions of JTG / T F20-2015 "Technical Specifications for Highway Pavement Base Construction". The lime described in the present invention can neutralize the P2O5 remaining in the phosphogypsum, so that the pH of the roadbed filler is neutral or weakly acidic (alkaline); on the other hand, it can act as an activator of mineral powder, activate the activity of the mineral powder, and enhance the early strength development of the filler.

[0014] The carbide slag described in the present invention is a byproduct of acetylene production by adding water to carbide. It is a major industrial waste residue produced in PVC production. Every ton of polyvinyl chloride produced will produce 1.2 tons of carbide slag (dry basis), which is a Class II general industrial solid waste. The alkaline physical and chemical properties of carbide slag neutralize and solidify the water-soluble phosphorus impurities in phosphogypsum. The removal of water-soluble phosphorus impurities can effectively optimize the microscopic morphology of gypsum and improve its strength. At the same time, carbide slag will also react with water-soluble phosphorus to form calcium phosphate, reducing the dissolution of soluble phosphorus.

[0015] The polycarboxylate water reducer of the present invention is a powder polycarboxylate water reducer. The polycarboxylate water reducer can change the crystal morphology, significantly reduce the porosity of the hardened gypsum, and effectively improve the pore structure of the hardened body, thereby helping to improve the mechanical strength and waterproof performance of the gypsum.

[0016] The water-absorbing and swelling agent used in the present invention can absorb water and swell. When added to the filler, it can fill the gaps between other raw material particles and make the structure more compact. When the filler meets water later, it can absorb the intruded water, which helps to increase its water stability. For example, sodium alginate is a byproduct of extracting iodine and mannitol from kelp or sargassum of brown algae. Studies have shown that sodium alginate can absorb more than 10 times its own volume of water and swell.

[0017] The present invention uses a waterproofing agent to change the surface of the phosphogypsum particles from hydrophilic to hydrophobic, blocking the interconnected pores in the phosphogypsum, thereby improving the water stability of the phosphogypsum. For example, sodium methyl silicate is an organic compound with a molecular formula of CH5SiO3Na. Sodium methyl silicate generates a polysiloxane hydrophobic film, which changes the surface of the phosphogypsum particles from hydrophilic to hydrophobic.

[0018] The metakaolin of the present invention is anhydrous aluminum silicate formed by dehydrating kaolin at an appropriate temperature (600-900°C). The active ingredients in the metakaolin are aluminum silicate and calcium hydroxide, which react to form hydrated calcite and secondary CSH gel with gel properties. These hydration products can greatly enhance the unconfined compressive strength of the filler.

[0019] The mineral powder described in the present invention is actually the abbreviation of granulated blast furnace slag powder. Granulated blast furnace slag is used as the main raw material, and a small amount of gypsum can be added to grind it into a powder of a certain fineness, which is called granulated blast furnace slag powder, referred to as slag powder, and belongs to volcanic ash active material. The mineral powder mainly used in the present invention is S95 grade mineral powder, which contains more active SiO2 and active Al2O3, and can react chemically with Ca(OH)2 at room temperature to generate stable hydrated calcium silicate and hydrated calcium aluminate. These ingredients help harden the mixture and increase its strength. At the same time, the particle size of the mineral powder is smaller than that of the phosphogypsum particles, and can be filled in the gaps between the phosphogypsum particles to form the densest stacking, which is conducive to the development of strength.

[0020] The curing agent for improving the water stability of phosphogypsum of the present invention is applied to high-dosage phosphogypsum roadbed filler.

[0021] The present invention provides a modified phosphogypsum using the curing agent, which is prepared by mixing the curing agent and the phosphogypsum in a mass ratio of 18-35:82-65.

[0022] The preparation method of the modified phosphogypsum of the present invention is: firstly, pretreating the phosphogypsum with a citric acid solution, then washing with clean water and drying, and finally directly mixing the dried phosphogypsum with the above-mentioned curing agent to obtain the modified phosphogypsum;

[0023] Among them, the mass of citric acid in the citric acid solution accounts for 1% to 2% of the mass of phosphogypsum; citric acid, as a pretreatment agent, can convert impurities such as phosphorus and fluorine into water-washable citrates, aluminates and ferrites, reducing the dissolution of harmful elements and ions in the later filler.

[0024] The specific preparation method of the modified phosphogypsum of the present invention is: first, pretreat the phosphogypsum with a citric acid solution at 30°C for 20 to 25 minutes, and then wash it with clean water for 3 times, each time for at least 3 minutes; the washed phosphogypsum is dried at 50°C, and after drying to a moisture content of the phosphogypsum of ≤1%, it is directly mixed with the above-mentioned curing agent to obtain the modified phosphogypsum.

[0025] The method for using the modified phosphogypsum of the present invention is as follows: according to the technical requirements of roadbed filler, a predetermined amount of water is added to the modified phosphogypsum, and the mixture is stirred evenly before use.

[0026] The beneficial effects of the present invention are as follows:

[0027] (1) The curing agent for improving the water stability of phosphogypsum prepared by the present invention forms calcium silicate hydrate and calcium aluminate hydrate through hydration between the components, which fills the space between the phosphogypsum particles, enhances the bonding ability between the raw materials, and significantly improves the road performance of the phosphogypsum. The unconfined compressive strength and bearing ratio of the solidified phosphogypsum are significantly improved, and under the specified compaction degree, it can fully meet the road performance technical requirements for roadbed fillers in JTG / T F20-2015 "Technical Specifications for Highway Pavement Base Construction".

[0028] (2) The curing agent prepared by the present invention reduces the dissolution amount of soluble P and soluble F in the phosphogypsum filler by converting the soluble P and soluble F in the phosphogypsum filler into insoluble salts, thereby ensuring the environmental protection requirements of the phosphogypsum filler for roadbed filling.

[0029] (3) The curing agent prepared by the present invention forms calcium silicate hydrate and calcium aluminate hydrate through hydration. On the one hand, it covers the phosphogypsum particles to prevent them from direct contact with water. On the other hand, it can fill the gaps between the phosphogypsum particles, improve the density, make it difficult for water to invade, reduce the strength loss of phosphogypsum after contacting water, and enhance its water stability. At the same time, the diaphragm can reduce the dissolution amount of uncured soluble P, F and other harmful elements and ions in phosphogypsum, further ensuring the environmental protection requirements of phosphogypsum filler for roadbed filling.

[0030] (4) The present invention can quickly and massively dispose of phosphogypsum, thus solving the environmental problems and land waste problems caused by the stacking of phosphogypsum. At the same time, it can greatly reduce the demand for sand and soil as roadbed filler, thus reducing the cost of roadbed construction. It has multiple benefits such as environmental protection, resource conservation, green development and reduced investment. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The compaction curves of the modified phosphogypsum prepared in Example 1 with different moisture contents and dry densities are shown. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0033] (I) Preparation of a curing agent for improving the water stability of phosphogypsum

[0034] A curing agent for improving the water stability of phosphogypsum, comprising the following components in parts by weight:

[0035]

[0036] The mineral powder is a gelling agent, and lime, carbide slag, polycarboxylic acid water reducer, water-absorbing swelling agent, waterproofing agent and metakaolin are additives.

[0037] The water-absorbing swelling agent is selected from a mixture of any one or more of sodium alginate, sodium carboxymethyl cellulose, and starch grafted acrylic acid copolymer.

[0038] The waterproofing agent is selected from any one or more of sodium methyl silicate, hexadecyltrimethylammonium chloride and sodium stearate.

[0039] The lime is slaked lime powder.

[0040] The carbide slag is a byproduct of producing acetylene by adding water to carbide, and is a major industrial waste residue generated in the production of PVC.

[0041] The polycarboxylate water reducer is a powdered polycarboxylate water reducer.

[0042] The metakaolin is anhydrous aluminum silicate formed by dehydrating kaolin as a raw material at a suitable temperature (600-900° C.).

[0043] The mineral powder is actually the abbreviation of granulated blast furnace slag powder.

[0044] The phosphogypsum curing agent of the present invention is applied to high-volume phosphogypsum roadbed filler.

[0045] A modified phosphogypsum using the above-mentioned curing agent is prepared by mixing the above-mentioned curing agent and the phosphogypsum in a mass ratio of 18-35:82-65.

[0046] The specific preparation method of the modified phosphogypsum is as follows: firstly, the phosphogypsum is pretreated with a citric acid solution at 30°C for 20 to 25 minutes, and then washed with clean water for 3 times, each time for at least 3 minutes; the washed phosphogypsum is dried at 50°C until the moisture content of the phosphogypsum is ≤1%, and then directly mixed with a curing agent to obtain the modified phosphogypsum;

[0047] The mass of citric acid in the citric acid solution accounts for 1% to 2% of the mass of the phosphogypsum.

[0048] Synthesis example 1

[0049] A curing agent for improving the water stability of phosphogypsum, comprising the following components in parts by weight:

[0050]

[0051] The water-absorbing swelling agent is sodium alginate, and the waterproofing agent is sodium methyl silicate.

[0052] Synthesis example 2

[0053] A curing agent for improving the water stability of phosphogypsum, comprising the following components in parts by weight:

[0054]

[0055]

[0056] The water-absorbing swelling agent is sodium carboxymethyl cellulose, and the waterproofing agent is hexadecyltrimethylammonium chloride.

[0057] Synthesis example 3

[0058] A curing agent for improving the water stability of phosphogypsum, comprising the following components in parts by weight:

[0059]

[0060] The water-absorbing swelling agent is a starch-grafted acrylic acid copolymer, and the waterproofing agent is sodium stearate.

[0061] Synthesis example 4

[0062] A curing agent for improving the water stability of phosphogypsum, comprising the following components in parts by weight:

[0063]

[0064] The water-absorbing swelling agent is sodium alginate, and the waterproofing agent is sodium methyl silicate.

[0065] Synthesis example 5

[0066] A curing agent for improving the water stability of phosphogypsum, comprising the following components in parts by weight:

[0067]

[0068]

[0069] The water-absorbing swelling agent is a mixture of sodium alginate and sodium carboxymethyl cellulose in a mass ratio of 1:1, and the waterproofing agent is a mixture of sodium methyl silicate and hexadecyltrimethylammonium chloride in a mass ratio of 1:1.

[0070] (II) Preparation of modified phosphogypsum

[0071] Example 1

[0072] A method for preparing modified phosphogypsum: firstly, pretreating the phosphogypsum with a citric acid solution at 30°C for 20 minutes, and then washing it with clean water for 3 times, each time for at least 3 minutes; drying the washed phosphogypsum at 50°C until the moisture content of the phosphogypsum is ≤1%, and then directly mixing it with the curing agent prepared in Synthesis Example 1 to obtain the modified phosphogypsum;

[0073] The amount of citric acid used accounts for 1wt% of the mass of phosphogypsum, and the ratio of phosphogypsum to curing agent is 80.3:19.7.

[0074] Example 2

[0075] A method for preparing modified phosphogypsum: firstly, pretreating the phosphogypsum with a citric acid solution at 30°C for 20 minutes, and then washing it with clean water for 3 times, each time for at least 3 minutes; drying the washed phosphogypsum at 50°C until the moisture content of the phosphogypsum is ≤1%, and then directly mixing it with the curing agent prepared in Synthesis Example 2 to obtain the modified phosphogypsum;

[0076] The amount of citric acid used accounts for 1wt% of the mass of phosphogypsum, and the ratio of phosphogypsum to curing agent is 77.3:22.7.

[0077] Example 3

[0078] A method for preparing modified phosphogypsum: firstly, pretreating the phosphogypsum with a citric acid solution at 30°C for 20 minutes, and then washing it with clean water for 3 times, each time for at least 3 minutes; drying the washed phosphogypsum at 50°C until the moisture content of the phosphogypsum is ≤1%, and then directly mixing it with the curing agent prepared in Synthesis Example 3 to obtain the modified phosphogypsum;

[0079] The amount of citric acid used accounts for 1wt% of the mass of phosphogypsum, and the ratio of phosphogypsum to curing agent is 73.2:26.8.

[0080] Example 4

[0081] A method for preparing modified phosphogypsum: firstly, pretreating the phosphogypsum with a citric acid solution at 30°C for 22 minutes, and then washing it with clean water for 3 times, each time for at least 3 minutes; drying the washed phosphogypsum at 50°C until the moisture content of the phosphogypsum is ≤1%, and then directly mixing it with the curing agent prepared in Synthesis Example 4 to obtain the modified phosphogypsum;

[0082] The amount of citric acid used accounts for 1.5wt% of the mass of phosphogypsum, and the ratio of phosphogypsum to curing agent is 68.2:31.8.

[0083] Example 5

[0084] A method for preparing modified phosphogypsum: firstly, pretreating the phosphogypsum with a citric acid solution at 30°C for 25 minutes, and then washing it with clean water for 3 times, each time for at least 3 minutes; drying the washed phosphogypsum at 50°C until the moisture content of the phosphogypsum is ≤1%, and then directly mixing it with the curing agent prepared in Synthesis Example 5 to obtain the modified phosphogypsum;

[0085] The amount of citric acid used accounts for 2wt% of the mass of phosphogypsum, and the ratio of phosphogypsum to curing agent is 68.05:31.95.

[0086] Comparative Example 1

[0087] Phosphogypsum filler without curing agent and pre-treatment with citric acid solution.

[0088] Comparative Example 2

[0089] A method for preparing modified phosphogypsum: mixing phosphogypsum that has not been pretreated with a citric acid solution with a curing agent prepared in Synthesis Example 1 to obtain the modified phosphogypsum;

[0090] The ratio of the phosphogypsum to the curing agent is 80.3:19.7.

[0091] Comparative Example 3

[0092] First, the phosphogypsum is pretreated with a citric acid solution at 30°C for 20 minutes, and then washed with clean water for 3 times, each time for at least 3 minutes; the washed phosphogypsum is dried at 50°C until the moisture content of the phosphogypsum is ≤1% to obtain the phosphogypsum filler without adding a curing agent.

[0093] Application Examples

[0094] We conducted tests on various road performance indicators. During the test, phosphogypsum needs to be pre-treated with citric acid and washed with water, and then dried to a certain moisture content for standby use. The specific process will not be repeated here.

[0095] During the test, the ratio of curing agent to phosphogypsum = 0-35:100-65 was used for the test, and it was noted that the total ratio of phosphogypsum to curing agent must be 100. Specific tests were carried out according to the mix ratios described in Examples 1-5 and Comparative Examples 1-3.

[0096] 1. Compaction test.

[0097] The modified phosphogypsum prepared in each embodiment and the phosphogypsum obtained in the comparative example were added with different amounts of water and mixed respectively. Figure 1 is the compaction curve of Example 1. Figure 1 It can be seen that the maximum dry density is 1.663g / cm 3 , the optimum moisture content is 13.07%. Then, compaction tests of Examples 2-5 and Comparative Examples 1-3 were carried out, and the results are shown in Table 1. The test results of Examples 1-5 and Comparative Example 2 are very similar, with a slight difference in the optimum moisture content between them, and the maximum dry density is basically the same, indicating that the change in the curing agent formula and the citric acid pretreatment have negligible effects on the maximum dry density and optimum moisture content of phosphogypsum. The maximum dry density of Comparative Example 1 is 1.638 g / cm 3 , the optimum moisture content is 12.45%, indicating that the curing agent has a great influence on the maximum dry density and optimum moisture content of phosphogypsum. The reason is that the curing agent fills the pores between the phosphogypsum particles, increases the density, and increases the maximum dry density; at the same time, the specific surface area of ​​the curing agent particles is larger, so the required water content increases, and thus the optimum moisture content increases.

[0098] Table 1 Compaction test results

[0099] Optimum moisture content (%) Maximum dry density Example 1 13.07 1.663 Example 2 13.05 1.664 Example 3 13.09 1.662 Example 4 13.13 1.667 Example 5 13.15 1.665 Comparative Example 1 12.45 1.638 Comparative Example 2 13.10 1.667 Comparative Example 3 12.49 1.642

[0100] 2. Unconfined compression test

[0101] For the modified phosphogypsum with the best moisture content and maximum dry density in Table 1 of the compaction test, an unconfined compressive test was carried out, and Table 2 is the test results of the unconfined compressive strength. The test includes 8 mix ratios (Examples 1-5, Comparative Examples 1-3), 4 compaction degrees (90%, 93%, 96%, 100%) and 2 curing methods (immersion in water on the last day and no immersion in water). The water stability coefficient K is the ratio of the unconfined compressive strength of immersion in water on the last day to that of no immersion in water. Under the same mix ratio, the unconfined compressive strength increases with the increase of compaction degree, and the water stability coefficient increases with the increase of compaction degree; under the same compaction degree, there is not much difference in the unconfined compressive strength, but the water stability coefficient is slightly different. The unconfined compressive strength of all embodiments reaches the technical requirements of JTG / TF20-2015 "Technical Specifications for Highway Pavement Base Construction" for the use of industrial waste slag stabilized materials as base and subbase for expressways and first-class highways (unconfined compressive strength-immersed base ≥1.1MPa, subbase ≥0.8MPa). In Comparative Examples 1 and 3, unmixed phosphogypsum curing agent is used, and the water stability coefficient is 0, and the water stability is poor; in Comparative Example 2, the phosphogypsum is not pretreated, which has little effect on the water stability of the modified phosphogypsum.

[0102] Table 2 Unconfined compressive strength test results

[0103]

[0104] 3. CBR test

[0105] The Chinese name is California bearing ratio, and the full name is CBR California bearing ratio. It is usually characterized by the material's ability to resist local load intrusion deformation, and uses the bearing capacity of standard crushed stone as the standard, and expresses the CBR value as a percentage of the relative value.

[0106] For the modified phosphogypsum with the best moisture content and the maximum dry density in the compaction test Table 1, a CBR test was performed, and Table 3 is the CBR test results of Examples 1-5 and Comparative Examples 1-3. It can be seen that the phosphogypsum curing agent of the present invention effectively improves the CBR value of the phosphogypsum filler, and the CBR value increases with the increase of compaction degree, and the CBR value difference between different embodiments at the same compaction degree is small.

[0107] Table 3 CBR test results

[0108] Compaction degree 90% Compactness 95% Compaction degree 100% Example 1 19.83 30.52 45.60 Example 2 20.15 31.36 44.52 Example 3 18.54 28.74 47.80 Example 4 19.16 32.15 46.50 Example 5 19.52 33.21 44.33 Comparative Example 1 0 0 0 Comparative Example 2 18.99 29.32 45.62 Comparative Example 3 0 0 0

[0109] 4. Soluble P and Soluble F Dissolution Test

[0110] When using phosphogypsum for roadbed, in addition to ensuring mechanical strength and water stability, it is also necessary to prevent the pollution risk of soluble P and soluble F. For the modified phosphogypsum with the best moisture content and maximum dry density in Table 1 of the compaction test, a soluble P and soluble F dissolution test was carried out.

[0111] Table 4 shows the dissolution test results of soluble P and soluble F of Examples 1-5 and Comparative Examples 1-3. By comparing the dissolution concentrations of soluble P and soluble F of Examples 1-5 and Comparative Examples 1-3, it is shown that the present invention can effectively solidify soluble P and soluble F. In particular, the dissolution concentration of Comparative Examples 1-3 is higher than that of Examples 1-5, and the dissolution concentration of Comparative Example 1 is higher than that of Comparative Example 3, indicating that the use of citric acid to pretreat phosphogypsum can effectively remove soluble P and soluble F in phosphogypsum.

[0112] Table 4 Dissolution test results of soluble P and soluble F

[0113] Soluble P (mg / L) Soluble F(mg / L) Example 1 0.008 0.055 Example 2 0.010 0.063 Example 3 0.006 0.047 Example 4 0.007 0.059 Example 5 0.011 0.052 Comparative Example 1 16.154 35.548 Comparative Example 2 0.131 0.550 Comparative Example 3 8.312 15.330

[0114] The following conclusions can be drawn from the above embodiments:

[0115] 1) Under the condition of appropriate curing agent weight ratio, the various road properties of the treated and improved phosphogypsum can meet the performance requirements of the base and sub-base fillers of different highway grades, and have good water stability, and can be used as the sub-base and base fillers of highways at all levels.

[0116] 2) The phosphogypsum curing agent significantly reduces the dissolution amount of soluble P and soluble F in the filler, ensuring the environmental friendliness of phosphogypsum used in highway base and subbase.

[0117] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A curing agent for improving the water stability of phosphogypsum, characterized in that: It is composed of the following components by weight: 6~8 parts of lime, 1~2 parts of calcium carbide slag, Polycarboxylate water reducer 0.1~0.2 parts, 0.2~0.3 parts of water-absorbing swelling agent, Waterproofing agent 0.4~0.5 parts, 2~3 parts of metakaolin, 10~20 parts of mineral powder; The waterproofing agent is selected from a mixture of any one or more of sodium methyl silicate, hexadecyl trimethyl ammonium chloride, and sodium stearate; The water-absorbing swelling agent is selected from a mixture of any one or more of sodium alginate, sodium carboxymethyl cellulose, and starch grafted acrylic acid copolymer.

2. A curing agent for improving the water stability of phosphogypsum according to claim 1, characterized in that: The lime is slaked lime powder, and its performance index meets the relevant provisions of JTG / T F20-2015 "Technical Specifications for Highway Pavement Base Construction"; The carbide slag is a byproduct of producing acetylene by adding water to carbide; The polycarboxylate water reducer is a powdered polycarboxylate water reducer; The metakaolin is anhydrous aluminum silicate formed by dehydrating kaolin at 600-900°C.

3. Use of the curing agent according to claim 1 or 2 in high-dosage phosphogypsum roadbed filler.

4. A modified phosphogypsum using the curing agent according to claim 1 or 2, characterized in that: The curing agent and phosphogypsum are mixed in a mass ratio of 18-35:82-65.

5. A method for preparing the modified phosphogypsum according to claim 4, characterized in that: include: Firstly, phosphogypsum is pretreated with a citric acid solution, then washed with clean water and dried, and finally the dried phosphogypsum is directly mixed with a curing agent to obtain the modified phosphogypsum; Among them, the mass of citric acid in the citric acid solution accounts for 1%~2% of the mass of phosphogypsum.

6. The preparation method according to claim 5, characterized in that: The specific preparation method is: first, pretreat the phosphogypsum with a citric acid solution at 30°C for 20 to 25 minutes, and then wash it with clean water for 3 times, each time for at least 3 minutes; the washed phosphogypsum is dried at 50°C, and after drying to a moisture content of the phosphogypsum of ≤1%, it is directly mixed with a curing agent to obtain the modified phosphogypsum.

7. A method for using the modified phosphogypsum according to claim 4, characterized in that: According to the technical requirements of roadbed filler, the modified phosphogypsum is added with a predetermined amount of water and stirred evenly before use.

Citation Information

Patent Citations

  • Citric acid with water washing technological method for removing fluorine impurity in phosphogypsum

    CN106977123A

  • High-volume phosphogypsum composite stable roadbed material and preparation method thereof

    CN111848082A

  • High-performance roadbed filler

    CN113292302A